L-arabinose isomerase from Lactobacillus parabuchneri and its whole cell biocatalytic application in D-tagatose biosynthesis from D-galactose. (June 2021) - Yuan, Jiao; Ravikumar, Yuvaraj; Zhang, Guoyan; Yun, Junhua; Zhang, Yufei; Zabed, Hossain M.; Qi, Xianghui
Abstract: l -arabinose isomerases (L-AIS) are enzymes that mediate the conversion of l -arabinose into l -ribulose and D-galactose into D-tagatose. The potential of L-AI from Lactobacillus parabuchneri CICC 6004 (LPAI) in D-galactose biotransformation using E. coli whole-cells was studied. The parameters investigated in this study were 1) the optimum pH, temperature, and cofactor specificity for maximum enzyme activity; 2) the D-tagatose biosynthesis from D-galactose using whole-cells containing LPAI. The results showed that with D-galactose, the purified LPAI showed the highest activity, 15.52 U/mg at pH 6.7, 45 °C, and necessitates 3 mM Ca 2+ as its cofactor. The K m, V max and K cat /K m values of LPAI for D-galactose were 5.4 mM, 35.5 U/mg and 2.8 mM −1 min −1, respectively, while the respective values for l -arabinose were found to be 4.3 mM, 63.1 U/mg and 5.9 mM −1 min −1 .The applicability of LPAI for D-tagatose synthesis was shown by using whole-cell biocatalyst approach. Under the optimum conditions, during one-stage biotransformation of D-galactose by E. coli whole cells, 39.0 g/L of D-tagatose was produced from 140 g/L of D-galactose after 50 h, which corresponded to the yield and productivity of 0.28 g/g and 0.78 g/L/h, respectively. Further addition of new cells into the reaction mixture in the second stage produced 54.0 g/L of D-tagatose after 100 h. The D-tagatose total yield and productivity were 0.39 g/g and 0.54 g/L/h, respectively. The results attained in this study showed LPAI as a potential candidate for the industrial production of D-tagatose. Highlights: A novel l -arabinose isomerase was expressed in E. coli BL21 (DE3) . Ca2+ was used as the co-factor in the biotransformation which was up to the food safety standard. The D-tagatose total yield and productivity were 0.39 g/g and 0.54 g/L/h, respectively.